Local stiffening of steel I-beams by using CFRP materials - Narmashiri, K.; Jumaat, Mohd Zamin; Ramli Sulong, Nor Hafizah (Advanced Materials Research, 2011)
This paper reports the experimental studies on the local stiffening of steel I-beams by using Carbon Fiber Reinforced Polymer (CFRP) strips. One of the problems which frequently occur for steel section is the large local deformation under point loads. To study the effects of applying CFRP for local stiffening, four steel I-beams were selected and tested to failure. The first beam had no steel stiffeners below the point loads and used as the control beam. The second beam had steel stiffeners and was not enhanced by using CFRP strip. The third and fourth beams had no steel stiffeners below the point loads and were strengthened on the compressive flanges by using two longitudinal CFRP strips. Also, the third and fourth specimens were strengthened on the web by using the latitudinal CFRP strips in the discrete and continual types, respectively. The results show that applying CFRP on the compressive flange and web increased the load bearing capacity and decreased the local and overall deformations appropriately. Also, the full-covering of the web seems to be the best type of web strengthening.